THE PLACE OF THE PRINCIPLE OF DUE DILIGENCE IN THE SYSTEM OF TAX ADMINISTRATION - Мороз, Віктор (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: the article is devoted to the study of the place of the principle of due diligence in the system of tax administration. Research methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical etc. Results: the concept of tax administration, constituent elements of the tax administration system, issues of tax administration in Ukraine, the essence of the principle of due diligence are determined, its origin and historical genesis are analyzed, the place of the principle of due diligence in the tax administration system and its relation to other elements. Discussion: the place of the principle of due diligence in the system of tax administration and its relationship with other elements of this system is established. Given the rapid development of the tax system of Ukraine and permanent reform of the functional structure of tax authorities, there is a need to systematize and improve scientific approaches to tax administration, which should result in the introduction of adequate institutional changes in tax relations and mechanisms for their implementation. One of the main principles of tax administration is the principle of due diligence, which determines the feasibility of studying the place of this principle in the system of tax administration and its relationship with other elements of the system of tax administration. On the one hand, the principle of due diligence is in line with the case law of the European Court of Human Rights and is designed to ensure a fair balance between public and private interests in the fight against tax evasion. However, on the other hand, the «blurring» of the criteria of due diligence and the abuse of power by the representatives of the fiscal authorities may be a reason for excessive tax burden on the taxpayer, who will be charged tax liabilities due to non-compliance with the principle of due diligence.